Geotechnical engineering of dams - Fell, Robin; MacGregor, Patrick; Stapledon, David; Bell, Graeme (Consulting dams engineer); Foster, Mark (CRC Press/Balkema, 2015)
"This book provides a comprehensive text on the geotechnical and geological aspects of the investigations for and the design and construction of new dams and the review and assessment of existing dams. The emphasis is on embankment dams, but much of the text, particularly those parts related to geology, can be used for concrete gravity and arch dams. The book aims to provide practising dam engineers and geologists with a practical approach, as well as to give university students an insight into the subject of dam engineering. The theoretical basis upon which design methods have been developed is included so readers develop a proper understanding of the limitations of the methods. All phases of investigation, design and construction are covered, from the initial assessment of a damsite and the development and carrying out of a detailed site investigation program, through to the preliminary and detailed design phases and ultimately the construction phase. The assessment of existing dams, including the analysis of risks posed by those dams, is also discussed. This wholly revised and significantly expanded 2nd edition includes a lengthy new chapter on the assessment of the likelihood of failure of dams by internal erosion and piping"--